2017
DOI: 10.1186/s12885-017-3523-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of pretreatment serum alanine aminotransferase/aspartate aminotransferase (ALT/AST) ratio and gamma glutamyltransferase (GGT) in patients with esophageal squamous cell carcinoma

Abstract: BackgroundThe levels of liver function tests (LFTs) are often used to assess liver injury and non-liver disease-related mortality. In our study, the relationship between pretreatment serum LFTs and overall survival (OS) was evaluated in esophageal squamous cell carcinoma (ESCC) patients.MethodsOur purpose was to investigate the prognostic value of the preoperative alanine aminotransferase/aspartate aminotransferase (ALT/AST) ratio and gamma glutamyltransferase (GGT) in ESCC patients. A retrospective study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 39 publications
5
43
1
Order By: Relevance
“…The expression of GGT has been shown to be upregulated after oxidative stress, but the signaling pathways implicated remain poorly characterized [47]. Previous studies have reported on the associations of serum GGT level with the risk of cancer [48]. Several potential mechanisms have been postulated for the relationship between GGT and cancer: As essential parts of the cellular defense apparatus, GGT and GSH combat oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of GGT has been shown to be upregulated after oxidative stress, but the signaling pathways implicated remain poorly characterized [47]. Previous studies have reported on the associations of serum GGT level with the risk of cancer [48]. Several potential mechanisms have been postulated for the relationship between GGT and cancer: As essential parts of the cellular defense apparatus, GGT and GSH combat oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…AAR plays a role in detecting extrahepatic diseases, which is also used for assessing the prognosis of patients with tumor surgery. Huang et al reported its use for the prognosis of patients with esophageal squamous cell carcinoma [38]. Lee et al and Gorgel et al reported the predictive effect of AAR in patients with urinary tract tumors after surgery [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…4 Since then, a large number of retrospective studies have examined the prognostic value of the De Ritis ratio in various cancer entities. [5][6][7][8][9][10][11] However, to the best of our knowledge its prognostic impact in patients with advanced PDAC has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%